Analisis VRIO Model Perusahaan Fintech dalam Menciptakan Keunggulan Kompetitif Berkelanjutan - Fenny Damayanti (Jurnal Sekretaris dan Administrasi Bisnis, 2021)
Technological developments have had a positive impact on business. By utilizing these technological advances, companies are able to carry out their business processes more efficiently. Financial company is one company that utilizes technological developments by changing its business platform or known as financial technology (fintech). To be able to maintain its existence in the business world, companies need to have a competitive advantage. Through the VRIO model, a company can analyze its internal and external strengths. Amartha, which is a peer to peer lending fintech company, is required to have the right competitive strategy in order to maintain a sustainable competitive advantage. The purpose of this study is to analyze the resource-based Amartha has through the VRIO model. This research is a qualitative research with a descriptive approach. Data collection techniques include literature studies, documentation studies from various sources such as the OJK report, the Indonesian fintech association. The results obtained from this study indicate that Amartha has utilized its resources in several aspects such as technological infrastructure, HR to maintain competitive advantage. In order for this competitive advantage to be sustainable, it is necessary to build more viable communication through social media as a step to increase the number of partners (borrowers and lenders). As a microfinancing company that serves more female partners, it is better to create ongoing training to educate more partners.